Reaktualisasi Strategi Pedagogi Qur'ani Rasulullah dalam Mengembangkan Kemampuan Berpikir Kritis Peserta Didik pada Era Post-Truth - Mustofa, Mustofa; Shohib, Muhammad (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
The post-truth era is characterized by the growing dominance of opinions, emotions, and subjective preferences over objective facts and evidence in shaping public perception. This condition has accelerated the spread of misinformation, hoaxes, and information manipulation, posing significant challenges to the intellectual and moral development of younger generations. Consequently, educational approaches are required not only to transmit knowledge but also to cultivate critical thinking skills, information literacy, and ethical awareness among learners. This study aims to reactualize the concept of Qur’anic dialectics as a pedagogical strategy employed by Prophet Muhammad (peace be upon him) to develop learners’ critical reasoning in addressing the challenges of misinformation in the post-truth era. The research adopts a qualitative approach using a library research method through the analysis of Qur’anic verses, Prophetic traditions, and relevant literature on Islamic pedagogy and contemporary critical thinking theories. The findings reveal that the Prophet’s pedagogical practices, manifested through dialogue (hiwar), exemplary conduct (uswah hasanah), analogical reasoning (amtsal), and rational argumentation, effectively foster critical, reflective, and verification-oriented thinking among learners. The integration of Qur’anic values with modern critical thinking frameworks provides a relevant educational strategy for strengthening intellectual and moral resilience against misinformation and hoaxes. Therefore, the reactualization of Qur’anic dialectics contributes not only to enhancing information literacy but also to nurturing a generation committed to truth, justice, and social responsibility in the digital age.